Climate Crises and Crypto-Colonialism: Conjuring Value on the Blockchain Frontiers of the Global South - Howson, Peter (Frontiers in Blockchain, 2020)
This commentary explores how climate crises are used to justify “crypto-colonialism,” whereby blockchain technology is used to extract economic benefits from those suffering the scars of historic colonial expansion in the Global South. These benefits include land, labor, data and other resources needed to facilitate capital interests elsewhere. As with past neoliberal development agendas imposing structural economic reforms, the contemporary crypto-colonial exercises discussed here are driven in pursuit of a common good – to protect the global commons and improve people’s lives. The paper explores how investors are drawn to the sustainable development frontiers – the code/spaces where crypto-colonial conjuring manifests. Blockchain is implicated within crypto-colonialism in three ways. Firstly, it plays into ongoing narratives of “green grabbing,” where local claims to resources are liquidated for green investments. Secondly, the technology perpetuates North-South trade and investment inequalities, and thirdly, a new power asymmetry is enabled by the technology through data colonialism and surveillance capitalism. In reviewing the spaces where crypto-colonialism manifests, the paper argues that despite being distributed, techno-ecological fixes are never placeless. How people configure, use, and are impacted by blockchain platforms is geographically contingent.